Hubungan Pola Asuh Demokratis Dan Self Esteem Dengan Kemandirian - Thesa Ujiani, Lena, Taufik Kasturi, S.Psi., M.Si., Ph.D (2017)
ABSTRACT The purpose of this study to determine the relationship of democratic parenting style and self esttem towards independence at Muhammadiyah University students who are doing COAS. This research is the quantitative study by using a questionnaire as the collecting data. The sample done by random sampling. This technique is used because the number of samples too broad. This technique was done using two phases, the determination of the sample and ascertaining the quantity of respondents in a sample that in question. Of the population of several samples of 109 as 65 Muhammadiyah University Surakarta, student medical schools are being run coas Hospital Sukoharjo willing to serve as the respondents. The result showed that from the results of the variable t known The foster democraticto exert an influence of 2,873 and variable self esteem of 5,401 with a value of 0,822 determinan ( 82,2 % ) .From the results of the t also be judged that the variable self esteem is the variable who has links strongest by independence in UMS medical student. Key words: The foster democratic, Self Esteem and Independence